Tomato wilt disease (Fusarium oxyporium f. sp. Lycopersici): A threat to tomato production and humanity - Falade, Moses Jimoh; Alabi, Bolaji Toyin (Journal of Pure and Applied Agriculture, 2025)
Tomato is one of the most important vegetable crops globally. Its production is constrained by several biotic and abiotic factors. Fusarium wilt is one of the most destructive diseases in tomato plants caused by Fusarium spp. The disease reduces the plant fruit yield significantly, it can wipe off a whole field completely during the endemic season or when the environment is favourable for the pathogen. The infected plant shows a wilting sign at the initial stage and later dies off. Difficulty in managing the disease could be attributed to its survivability of the pathogen on different mediums for a long period and its existence in diverse pathogenic races coupled with poor understanding of its management by most tomato growers. The use of chemical fungicides are majorly relies on as an effective method in managing tomato wilt and the method is not eco-friendly. This review explained various methods that can be adopted in managing the disease without jeopardizing human health and the environment at large. The review provides diverse control methods to be integrated in managing Fusarium wilt. Understanding the biology and management of fusarium wilt in tomatoes will reduce the great loss it causes in tomato production. By integrating biological control methods, crop rotation, resistant tomato varieties, and cultural practices, farmers can significantly reduce the severity of the disease. Additionally, increasing awareness and knowledge about Fusarium wilt among tomato growers is essential for improving disease management strategies.